Kinematic analysis of hurdle clearance of 60-m hurdles in elite hurdle sprinters during world indoor championships 2010 - Kuitunen, S.; Poon, S. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Previous studies have examined the biomechanical variables of sprint hurdling of world-class athletes (Mero, & Luhtanen, 1986; McDonald, & Dapena, 1991). However, less is known about the factors that differentiate the performance among elite hurdle sprinters. Salo, Grimshaw, & Marar, (1997) compared international and national/county level female hurdlers and found that better hurdlers use greater take-off distance, which enables lower take-off angle and greater horizontal take-off velocity. Our previous analysis between international level hurdlers and decathletes revealed an opposite pattern of greater take-off distance for decathletes than for hurdlers (Kuitunen, Palazzi, Poon, & Peltola, 2007). The present study aims to examine the possible differences in hurdle clearance between different level of elite hurdle sprinters.